Una aproximación a la documentación en la comunicación política - Torregrosa Carmona, Juan Francisco; García Jiménez, Antonio (Documentación de las Ciencias de la Información, 2007)
This article offers an overview of the role of “Documentation” in Political Communication, specifically as used by political parties, from a descriptive perspective. Using as a framework the importance of “Documentation” in Corporate Communication, the article offers a review on the characteristics, processes and functions of “Documentation” in the day to day work of political parties, including recent trends, such as the Internet.